2015
DOI: 10.1124/mol.114.096743
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Diethylstilbestrol during Pregnancy Modulates MicroRNA Expression Profile in Mothers and Fetuses Reflecting Oncogenic and Immunological Changes

Abstract: Prenatal exposure to diethylstilbestrol (DES) is known to cause an increased susceptibility to a wide array of clinical disorders in humans. Previous studies from our laboratory demonstrated that prenatal exposure to DES induces thymic atrophy and apoptosis in the thymus. In the current study, we investigated if such effects on the thymus result from alterations in the expression of microRNA (miR). To that end, pregnant C57BL/6 mice who were exposed to DES and miR profiles in thymocytes of both the mother and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 48 publications
1
22
0
Order By: Relevance
“…In brief, total RNA including miRs from inguinal LNs were isolated using miRNeasy kit and following the protocol of the company (QIAGEN, Valencia, CA). Next, miR arrays were performed and data were analyzed using hierarchical clustering, as described previously (33, 44, 55). miR arrays data were submitted to Array Express (Accession number: E-MTAB-4076; webpage: http://www.ebi.ac.uk/arrayexpress/submit/overview.html; https://www.ebi.ac.uk/fg/annotare/).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In brief, total RNA including miRs from inguinal LNs were isolated using miRNeasy kit and following the protocol of the company (QIAGEN, Valencia, CA). Next, miR arrays were performed and data were analyzed using hierarchical clustering, as described previously (33, 44, 55). miR arrays data were submitted to Array Express (Accession number: E-MTAB-4076; webpage: http://www.ebi.ac.uk/arrayexpress/submit/overview.html; https://www.ebi.ac.uk/fg/annotare/).…”
Section: Methodsmentioning
confidence: 99%
“…The selection of these two miRs was also based on their binding affinity with complementary sequences of their respective genes (miR-490:FoxP3 and miR-1192: IL-17). The transfections were pursued as described earlier (33, 44, 55, 56). Briefly, T cells purified from LNs of mBSA-immunized mice were either transfected with scrambled miR (MOCK) or with mature miR-490 mimic, miR-490 inhibitor using Transfection kit from QIAGEN and following the protocol of the company (QIAGEN).…”
Section: Methodsmentioning
confidence: 99%
“…Due to exposure to DES may cause DNA methylation, the fetal genome is allowed to encode multiple defects, which may not be expressed before a certain period of time (puberty, for example) [95]. Studies have shown that microRNA levels may change due to the effects of DES, and microRNA-mediated upregulation of Fas and its ligands leads to increased autophagy and apoptosis [96].…”
Section: Diethylstilbestrolmentioning
confidence: 99%
“…We purchased Diethylstilbestrol (DES) powder and Acridine Orange (AO) solution from Sigma-Aldrich (Sigma-Aldrich, St. Louis, MO). DES suspended in corn oil was used for in vivo studies and DES suspended in Dimethyl sulfoxide (DMSO) was used for in vitro studies, as described (Singh et al, 2012, 2015a,b). The culture medium (RPMI1640, Penicillin/ Streptomycin, HEPES (4-(2-hydroxyethyl)-1-piperazineethanesulfonic acid), L-glutamine, Fetal Bovine Serum (FBS), and PBS (Phosphate-buffered saline) were purchased from Invitrogen Life Technologies (Carlsbad, CA).…”
Section: Methodsmentioning
confidence: 99%